Dimensionless variable groups for the free-fall grain dryer - Meesukchaosumran, Supitchar; Chitsomboon, Tawit (International Journal of Agricultural and Biological Engineering, 2019)
Dimensionless variable groups (DGs) of free-fall grain dryer were developed by using the characteristic scaling method and engineering intuition. These DGs were intended for the analyses of drying characteristics and sizes of this dryer. Experiments of the free-fall rough rice dryer were carried out using different drying chambers (small and medium scales), drying air temperatures (100°C-150°C), and drying air speeds (1-3 m/s). Experimental data were used to study relationships and to validate similarities among these DGs. The results of the study showed the five appropriate dimensionless variables representing and describing the drying mechanism of the free-fall dryer. These DGs could be applied to design and analyze scaling up the dryer. In addition, the dimensionless correlation was established to predict the moisture contents of rough rice while being dried by the free-fall dryer. The predicted values from this correlation were in relatively good agreement with the experimental data under the proposed drying conditions (R2=0.989, MRD=1.82% and RMSE=0.0168).Keywords: dimensionless variable, similarity, free-fall dryer, rough riceDOI: 10.25165/j.ijabe.20191204.4188Citation: Meesukchaosumran S, Chitsomboon T. Dimensionless variable groups for the free-fall grain dryer. Int J Agric & Biol Eng, 2019; 12(4): 197–204.